A Systematic Literature Review: Limitation of Video Conference - Rezki Yunanda; Ian Jeremiah Cahyadi; Bryan Theophilllus; Jason Oei; Ivan Sebastian Edbert; Alvina Aulia (Bina Nusantara University, 2022)
The Covid-19 pandemic that has hit the world has resulted in limited human activities. Video conferencing is one solution for carrying out activities. Video conferencing helps people reduce the spread of Covid-19 and connects people. With video conferencing, people can meet without being limited by space and time. However, video conferencing still has various drawbacks, such as the inability to interact. Because we only see the video, the lack of technology due to video conferencing requires us to use technology such as computers or cell phones that a stable and fast internet network must support to ensure smooth video conferencing. In this paper, the researcher conducted a literature study to determine the limitations of video conferencing. The results show the various reasons for video conferencing restrictions. Some of these reasons are experienced by lecturers, students, or the lack of infrastructure. Students are challenged to improve their level of study due to the lack of technological support that supports only using video conferencing.